Framework for logistics coordination and distribution mobile application in disaster management - Kartiwi, Mira; Gunawan, Teddy Surya (2013)
In the recent years, hundreds to thousands of people have been killed in many calamities across Asian region, such as tsunami, floods, earthquake and so on. These natural disasters have become great challenges, particularly to those developing countries as many are lacking of an efficient disaster management system and disaster recovery plan that will help in times of need. Among the common challenges in managing emergency relief response is the coordination of logistics distribution on the field. Often there is hoarding of assistance from a number of institutions at a particular location or village but not well distributed to other areas, thus led to waste and inefficiencies. As a result, many of the aids supplied could not reach its intended target. Therefore, it is the aim of this study to propose a coordination framework for logistics distribution in disaster management, and to overcome communication problems among and between rescue, volunteers and humanitarian teams, particularly in logistics distribution. The proposed framework will be implemented in the form of a prototype for mobile application.